UKRAINE IS A CONTRIBUTOR TO INTERNATIONAL SECURITY - Гнилицька, Анастасія; Михайлюк, Олена (Modern engineering and innovative technologies, 2023)
The article defines the position of Ukraine in the international arena as an independent actor capable of acting in the process of changes in the word order. This is due to the active position of the state and its ability to effectively cooperate with oth